2013
DOI: 10.1038/gene.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

miR-31 regulates interleukin 2 and kinase suppressor of ras 2 during T cell activation

Abstract: MicroRNA (miRNA) has an important role as a master regulator of gene expression in immune system and is upregulated during T cell differentiation, however its function is not clear yet. In this study, the contribution of miR-31 in T cell activation was investigated. miR-31 was upregulated during the activation of primary T lymphocytes upon T-cell receptor (TCR) stimulation. Ectopic expression of miR-31 increased the expression of interleukin (IL)-2, while knockdown of endogenous miR-31 decreased the IL-2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Consistent with our findings for mice, stimulation via the TCR induces miR-31 expression in human T cells 46 . Blocking miR-31 expression in human T cells might prove therapeutically useful for boosting immune responses during chronic viral infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our findings for mice, stimulation via the TCR induces miR-31 expression in human T cells 46 . Blocking miR-31 expression in human T cells might prove therapeutically useful for boosting immune responses during chronic viral infection.…”
Section: Discussionsupporting
confidence: 92%
“…Because CD8 + T cells progressively lose the ability to secrete the cytokines IL-2 and TNF and, finally, IFN-γ 40 during chronic viral infection, we assessed the functionality of antigen-specific CD8 + T cells in wild-type, Mir31 −/− and Mir31 fl/fl Cd4 Cre mice on day 28 or 30 after infection with LCMV clone 13. Splenocytes from infected mice were pulsed ex vivo with the peptides GP33 and GP276 (from LCMV glycoprotein) and NP396 (from LCMV nucleoprotein), followed by intracellular cytokine staining for IFN-γ, TNF and IL-2 in CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This repression is reversed upon T-cell activation that downregulates miR-181c expression [38]. By contrast, miR-31 was found to be upregulated upon TCR stimulation and to increase IL-2 production [39]. By directly targeting kinase suppressor of ras 2, a repressor of COT/TPI2 signaling, miR-31 was shown to enhance the activity of nuclear factor of activated T cells (NFAT), which in turn promotes IL-2 expression.…”
Section: Mirna Regulation Of Il-2mentioning
confidence: 99%
“…The AS isoform (344 bp) may have a different biological half-life or transportability, leading to the decreased expression of TCRf mRNA and protein Tsuzaka et al, 2002). Since it has been reported that miRNA can repress the translational of multiple protein-coding mRNAs by sequence-specific binding to the 3¢UTR and may be associated with prognosis, it remains an open question whether miRNA has played a role in regulation mechanism (Gimenes-Teixeira et al, 2013;Xue et al, 2013). This finding indicates that the abnormal expression and dysfunction of the TCRf related to the 3¢UTR play a role in T-cell immune disorders.…”
Section: Introductionmentioning
confidence: 99%